Performance Effects of High Performance Work Systems on Committed, Long-Term Employees: A Multilevel Study - Pahos, Nikolaos; Galanaki, Eleanna (Frontiers in Psychology, 2022)
Even though effects of High Performance Work Systems (HPWS) on employee performance have been widely investigated, there is no consensus on how this link is achieved. Drawing on Social Exchange Theory (SET), this paper attempts to shed more light in this relationship by investigating the mediating role of affective, normative, and continuance commitment in the relationship between HPWS and employee performance. Moreover, the potential moderating role of employee tenure on the HPWS—organizational commitment link is examined. Using data from 342 subordinates and 115 supervisors from 111 service organizations in Greece, our multilevel analysis shows that affective commitment fully mediates the relationship between HPWS and employee performance. In addition, employee tenure positively moderates the relationships between HPWS and affective and normative commitment. The paper discusses theoretical implications and provides recommendations for practitioners.